Photoionization and photofragmentation of multiply charged Lu3N@C80 ions. (August 2015) - Hellhund, J; Borovik, A; Holste, K; Klumpp, S; Martins, M; Ricz, S; Schippers, S; Müller, A
Synopsis: Relative cross sections for photoionization and photofragmentation of endohedral fullerene Lu3 N@C80 q + (q=1, 2, 3) ions have been measured employing the new photon-ion spectrometer PIPE at PETRA III. Prominent structures related to the carbon K-shell ionization threshold were observed in the energy range 280 to 330 eV.